Restructuring and managing the telecommunications sector - Wellenius, Bjorn; World Bank. (Washington, D.C. World Bank, 1989)
The object of this volume is to identify key telecommunications policy issues and to consider alternatives for sector development. The authors present the experiences of various countries that have restructured their telecommunications sector to adjust to the changing environment. The volume is organized into four parts. Part I establishes the conceptual framework; examines and discusses national policy issues, sector structure issues; analyzes service competition; and proposes a regulatory structure for the orderly development of this complex and competitive sector. Part II describes the experience of industrialized countries with telecommunications sector reform. Part III presents the experiences of developing countries. Part IV concludes by summarizing the alternatives for the future that are open to the developing world.
Based on a seminar held in Kuala Lumpur, Malaysia, Nov. 17-19, 1987.
Electronic reproduction.
Keywords: Telecommunication -- Asia; Telecommunication policy -- Asia; Electronic books